Functional coordination between leaf traits and biomass allocation and growth of four herbaceous species in a newly established reservoir riparian ecosystem in China. Issue 23 (8th November 2018) - Xiong, Gaoming; Zhang, Aiying; Fan, Dayong; Ge, Jielin; Yang, Dan; Xie, Zongqiang; Zhang, Wangfeng
Abstract: The flood‐dry‐flood cycle in the reservoir riparian zone (RRZ) of the Three Gorges Dam has dramatically altered the riparian ecosystem structure and composition. Previous field studies have shown that leaf traits varied greatly and were restricted to the lower‐investment and faster‐return end of the global leaf spectrum, which are typical characteristics of fast‐growing species. However, it is unclear as to the mechanism underpinning the growth potential of these species and how it will respond to soil nutrient availability and temperature. Here, we linked the plant functional traits of four representative dominant C4 herbaceous species ( Setaria viridis, Echinochloa crusgalli, Cynodon dactylon and Hemarthria altissima ) to their relative growth rates (RGR) under ambient and elevated temperatures, with different nitrogen and phosphorus levels, to explore the potential mechanism of species growth in the newly established reservoir riparian ecosystem in the Three Gorges Reservoir Area, China. We grew seedlings of these species in four open‐top chambers, with three levels of nutrient supplies under two temperature gradients (ambient temperature and an elevated temperature of 4°C). We found that the responses of the RGR and plant traits to soil N and P supply levels and temperature varied considerably among studied species. E. crusgalli displayed the lowest RGR associated with relatively low specific leaf area (SLA), leaf nitrogen content (LN), stem mass ratio (SMR), and high leaf mass ratio (LMR) and was less affected by soil N and P supply levels and temperature. C. dactylon and H. altissima showed the highest RGR compared to the other two species grown at the substrate of N = 0.4 mg/g, P = 0.2 mg/g at ambient air temperature, associated with a relatively high SMR, low LMR and low plant carbon content (PCC). However, the RGR advantage of the two species was diminished at elevated temperatures, while S. viridis showed the highest RGR compared to the other species. Across all datasets, the RGR had no association with the leaf area ratio (LAR) and SLA. The RGR also showed no significant relationships with the LN and leaf phosphorus content (LP). On the other hand, the RGR was captured adequately by the SMR, which can therefore be considered as a powerful functional marker of species' functioning in this newly established reservoir riparian ecosystem. Our study provides some insight into the underlying mechanisms of species growth in reservoir riparian ecosystems. Abstract : We linked plant functional traits of four representative dominant C4 herbaceous species ( Setaria viridis, Echinochloa crusgalli, Cynodon dactylon and Hemarthria altissima ) to their relative growth rate, under ambient and elevated temperatures. The RGR was captured adequately by the SMR, which can therefore be considered as a powerful functional marker of species' functioning in this newly established reservoir riparian ecosystem.